The rational development of molecularly imprinted polymer-based sensors for protein detection. - Whitcombe, Michael J.; Chianella, Iva; Larcombe, Lee; Piletsky, Sergey A.; Noble, James; Porter, Robert; Horgan, Adrian (Royal Society of Chemistry, 2011)
The detection of specific proteins as biomarkers of disease, health status, environmental monitoring, food quality, control of fermenters and civil defence purposes means that biosensors for these targets will become increasingly more important. Among the technologies used for building specific recognition properties, molecularly imprinted polymers (MIPs) are attracting much attention. In this critical review we describe many methods used for imprinting recognition for protein targets in polymers and their incorporation with a number of transducer platforms with the aim of identifying the most promising approaches for the preparation of MIP-based protein sensors (277 references).
Keywords: molecularly imprinted polymers, MIPs, sensors, biosensors, protein, protein detection, epitope, analytical chemistry, polymers, plastic antibodies